The immature stages of Micropygomyia (Coquillettimyia) chiapanensis (Dampf) (Diptera: Psychodidae, Phlebotominae) - Oca-Aguilar, Ana Celia Montes De; Rebollar-Téllez, Eduardo A.; Ibáñez-Bernal, Sergio (Zootaxa, 2016)
The egg exochorion, larval instars and pupa of the phlebotomine sand fly Micropygomyia (Coquillettimyia) chiapanensis (Dampf) are described and illustrated based on specimens collected in the locality of Farallón, municipality of Actopan, Veracruz, Mexico. Morphology of fourth instar larval mouthparts, particularly the incisor lobe and molar lobe shape of mandible, could be important for species identification of immature Phlebotominae. In this work is compared the pupal chaetotaxy of Mi. chiapanensis with other species previously described. The fourth instar larva of Mi. chiapanensis is compared with other species of this genus, the most important differentiating characters being the size, shape and position of the abdominal dorsal internal seta.